ANALISIS KOMPARATIF LEKSEM “KEPALA (头)” DALAM BAHASA INDONESIA DAN MANDARIN (Aspek Kajian Semantik) - Noni, Nur Nasharuddin; Fatoni, Ahmad Sirfi; Ernawati, Ernawati (Wen Chuang:Journal of Foreign Language Studies, Linguistics, Education, Literatures, Cultures, and Sinology, 2024)
This article provides a comparison analisys of the lexeme "Head (头)" in Indonesian and Mandarin.With a qualitative approach, this research can explore the differences and similarities between theuse of the lexeme "head" in the two languages. Using qualitative methods, it will provide an in-depthdescription of the basic meaning focus and meaning variations of the use of the word "Head (头)" inthe semantic context of each language. Data was collected and analyzed from representative text andliterature sources in Indonesian and Mandarin. The research results show that, although both havesimilar basic meanings as parts of the human body, the words "Head (头)" in Indonesian andMandarin can show variations in meaning in everyday use, and in linguistic expressions. Thesedifferences may reflect differences in cultural thinking and social values related to the concept of"Head 头" in the societies of the two languages. This research provides deeper insight into thelinguistic and cultural differences between Indonesian and Mandarin, with the hope that it canprovide a basis for better understanding in the context of translation and cross-cultural interaction.Keywords: Lexeme“Kepala (头)”, Semantic, Comparative Analysis.